Photometric and Spectroscopic Investigation of the Dwarf Nova HS 0218+3229: A Short Review - N. Katysheva; S. Shugarov; N. Borisov; M. Gabdeev; P. Golysheva (Acta Polytechnica CTU Proceedings)
This paper is devoted to the study of the cataclysmic variable HS 0218+3229 using the photometric and spectroscopic observations.